Friday

April 25, 2014

April 25, 2014

Posted by **Chelsea** on Saturday, February 12, 2011 at 10:38am.

#1 (4y-3)/8 + (3)/(4y) = (y+3)/2

#2 5/(2x-1) = 1 - (8x-16)/(10x-5)

- algebra -
**Reiny**, Saturday, February 12, 2011 at 11:08amin each case find the LCD , then multiply each term by that.

I will do the #2

5/(2x-1) = 1 - (8x-16)/(10x-5)

5/(2x-1) = 1 - (8x-16)/(5(2x-1) )

LCD = 5(2x-1)

5/(2x-1)*5(2x-1) = 1*5(2x-1) - (8x-16)/(5(2x-1) )*5(2x-1)

25 = 10x - 5 - (8x-16)

14 = 2x

x = 7

**Related Questions**

algebra - solve the following using substitution 8x-4y=16 y=2x-4 8x-4(2x-4)=16 ...

Algebra - A few questions on simplifying rational expressions... 1). 15x^2/10x ...

math 30 - Help please i need to write 4x^2 -y^2 -8x -4y +16 =0 in standard form....

Algebra - Please look at the following simplification of an algebraic expression...

math - Not sure about this... Need to solve by substitution 8x - 4y = 16 y = 2x...

Algebra - I thought number 4 on this list was incorrect but didn't know how to ...

algebra - Solve by substitution: 8x - 4y =16 y=2x -4

Algebra - How to solve by substitution: 8x - 4y = 16 y = 2x - 4

Algebra - How do I solve the following by substitution: 5x -2y =-5 y - 5x = 3 8x...

math - Rational expressions in lowest terms 4y ------------ 2xy + 4y